Production of lactic acid by immobilized lactic acid bacteria in modified chitosan beads - Rusmin, Ruhaida; Zakaria, Zainora (SSM International Publication, India, 2008)
Lactic acid has been widely used in numerous applications, for example in food industry, pharmaceutical, cosmetics and production of biodegradable plastic. Worldwide production of lactic acid is mostly through the fermentation of lactic acid bacteria. However, during the food processing stages, the lactic acid bacteria face inhibition problems caused by contaminants. Therefore, immobilization of lactic acid bacteria by entrapment within polymer matrix was selected to minimize this problem. In this study, lactic acid bacteria were immobilized in chitosan which is a biopolymer derived from the deacetylation of chitin. The chitosan beads were prepared by dropping chitosan solution in sodium pyrophosphate. The effect of modifications of chitosan beads by adding polyvinyl alcohol (PVA) and crosslinking with glutaraldehyde (Glu) in strengthening the beads for the fermentation process were studied. Modification of beads with PVA and Glu to enhance their mechanical strength showed positive result. Comparing the different types of beads, the Chitosan-Glu beads were found to maintain its shapes after the second cycle of fermentation, but produced the lowest amount of lactic acid, which is 315 x 10-3 g /L